PELAYANAN SOSIAL BAGI ANAK YANG DILIBATKAN DALAM PERDAGANGAN NAPZA Pengalaman Bekerja Bersama Anak Jalanan di Rumah Pendampingan Sementara di Jakarta Timur - Hari Harjanto Setiawan (Sosio Informa, 2007)
Indonesia’s main policy in dealing with drug problems has been try to reduce abuse and dealing in drugs through enforcement of a number of law. The main problem of the current law is the children are not well protected and it does not distinguish between a child and an adult.However, the newly child protection Act No.23/2003, defines children’s involvement in the production, sale and trafficking of drugs as an act of victimization. Most children are in the situation because of adult pressure and/or wider social factors. Some children become a courier because their parents sell drugs for themselves. Peer pressure and pressure from adults in the community is very important. At same time, the communities do not see the issue as significant.Key words : child drugs trafficking (CDT), social work service, victimization.